A sensitivity-enhanced heterologous immunochromatographic assay based on a monoclonal antibody for the rapid detection of histamine in saury samples1. Issue 96 (17th October 2015) - Luo, Lin; Yang, Jin-Yi; Xiao, Zhi-Li; Zeng, Dao-Ping; Li, Yong-Jun; Shen, Yu-Dong; Sun, Yuan-Ming; Lei, Hong-Tao; Wang, Hong; Xu, Zhen-Lin
<x xml:space="preserve">Abstract</x> An immunochromatograhic strip for rapid detection of histamine based on a sensitive monoclonal antibody against p-nitrobenzoylated histamine was firstly reported.